The politics of spiritual work in Christian movements - Linjakumpu, Aini (Routledge focus on religion, 2026)
"This book examines how three conservative Christian movements - Jehovah's Witnesses, Conservative Laestadians, and the Old Order Amish - attribute spiritual meanings to both paid employment and voluntary work, and how work functions as a tool of governance within these communities. A central concept developed in the book is spiritual work, used to describe forms of labour imbued with religious meaning and purpose. The book offers a detailed analysis of how religious interpretations of work regulate members' lives and sustain internal power dynamics. By tracing both the theological roots and social consequences of these interpretations, the study demonstrates that work is not merely an economic necessity but a central component of the moral and spiritual order within these movements. Framed by perspectives from the study of power and governance, the book identifies three key dimensions through which governance operates via work: shaping individual spirituality, reinforcing communal belonging and cohesion, and regulating the boundary between the religious community and the outside world"-- Provided by publisher